When God Became White: Dismantling Whiteness for a More Just Christianity: Oleh Grace Ji-Sun Kim - Situmeang, Rynaldi Mahardika (Indonesian Journal of Theology, 2025)
A book review of When God Became White: Dismantling Whiteness for a More Just Christianity.